ANALISIS FORECASTING PENJUALAN GUNA MEMINIMALISIR KERUGIAN AKIBAT KEKURANGAN STOK MENGGUNAKAN METODE MOVA DAN WMA (STUDI KASUS PADA TOTAL BUAH SEGAR CABANG CIKARANG PENJUALAN JERUK WOKAM) - Nur Alya Rahmah (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STIE Pontianak, 2023)
In Indonesia, citrus fruits occupy the second level, which is the most consumed fruit with an average of 12.57 grams/capita/day. Lately the type of orange that is popular in Indonesia is wokam orange. Wokam oranges are citrus fruits imported from China. This type of orange can only be found in large fruit stores or supermarkets. Total Buah Segar is a large fruit shop that has several branches, one of which is Total Buah Segar Cikarang branch. Total Buah Segar Cikarang branch sells a variety of quality fruits, one of which is the popular wokam orange. Of course, its popularity can also cause problems in terms of stock inventory, namely there is often a shortage of wokam orange stock in Total Buah Segar Cikarang branch. Therefore, the management of Total Buah Segar Cikarang branch needs a sales forecast in order to determine the supply of wokam oranges in order to meet consumer demand. The method used in this study is a quantitative descriptive method. The calculation of forecasting the sales of wokam oranges uses the MOVA and WMA methods. Precise forecasting results are obtained, namely the WMA method from determining the smallest MAD, MSE, and MAPE values. So that Total Buah Segar Cikarang branch can consider the results of forecasting to make decisions regarding the supply of wokam oranges in the future.